Arab Hadrami, nasionalisme Indon PERGERAKAN ARAB HADRAMI MEMPERJUANGKAN IDENTITASNYA TAHUN 1934 -1942 - Zahra Nabila Fatin; Mukhamad Shokheh (Historia, 2027)
This study examines the transformation of the identity of the Arab Hadrami community in the Dutch East Indies from a diaspora-oriented identity toward a more inclusive Indonesian national identity during the early 20th century until 1942, using a qualitative historical method. Prior to 1934, the community tended to maintain an exclusive social identity with strong ties to Hadramaut. A significant turning point occurred with the Arab Youth Pledge of 1934, which encouraged younger generations of Arab descendants to identify themselves as part of the Indonesian nation. In the period between 1934 and 1942, their integration became more evident through the roles of organizations, intellectual figures, and participation in socio-political movements. These findings indicate that Indonesian nationalism developed in an inclusive manner by involving diverse ethnic groups, and highlight the important contribution of the Arab Hadrami community in shaping Indonesia’s national identity.